Influence Of Head teachers’ Autocratic Leadership Style On Implementation Of Inclusive Education In Public Primary Schools In Uasin Gishu County, Kenya - Agen'go, Ogony Maurice; Buhere, Pamela; Aloka, Peter Jairo (International Journal of Education and Research, 2019)
Kenyan schools have been encouraged to the pressure of inclusion to embrace integration of all learners including those with disabilities. The problem is that, despite the adoption of this policy in Kenya (2009), realization of this noble idea remains dismal, with most schools hardly achieving the basic objective of inclusion. Unpublished report from Uasin Gishu County (2015) indicates a low level of implementation of inclusive education primary schools. The role of head teachers in the implementation of inclusive education remains crucial. They are undoubtedly the central person in all the leadership and team work exhibited in any inclusive school. The purpose of this study therefore was to establish the influence of autocratic leadership style on the implementation of inclusive education in Uasin Gishu County, Kenya. The study was anchored on Lewin’s leadership theory. The study adopted Concurrent triangulation design within the mixed method approach. The target population for the study comprised 4909 teachers in public primary schools and 464 senior teachers totaling up to 5373. The sample size comprised 491 teachers stratified sampled, 10 senior teachers systematically randomly sampled and a sample size of 501 was used. Data collection instruments were questionnaires and interview schedules. Content, construct and face validity was ensured by expert judgment. Reliability was ensured by Cronbach Alpha method and reliability coefficients were all above 0.7. Quantitative data was analyzed by descriptive statistics and inferential statistics such as Pearson correlation and liner regression while Qualitative data was analyzed thematically. The results indicate da statistically significant negative correlation between the head teachers’ Autocratic leadership style and implementation of inclusive education (n=368; r =.401; p =.001). The study recommended that ministry of education through Quality Assurance and Standards Officers shoulder sensitize teachers on better leadership practices that can encourage implementation of inclusive education.
Keywords: implementation; inclusive; education; autocratic; leadership